2012
DOI: 10.1007/s00284-012-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Fatty Acids Promote the Phagocytosis of P. aeruginosa and R. equi by RAW264.7 Macrophages

Abstract: In the present study, using the murine monocyte/macrophage cell line RAW264.7 as a model system, we analyzed the phagocytosis rate and the bactericidal capacity of polyunsaturated fatty acids (PUFA)-enriched macrophages against Pseudomonas aeruginosa and Rhodococcus equi. The P. aeruginosa strain ATCC 10145, the virulent R. equi strain ATCC 33701, and the non-virulent R. equi strain ATCC 6939 were examined. Flow cytometric detection of intracellular microorganisms in combination with viability assays were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…However, to our knowledge, the present study is the first to address the effects of ω3 FAs on microglial phagocytosis of A␤ 42 and on their M1/M2 phenotype. Several studies have shown stimulatory effects of ω3 FAs on other types of phagocytic cells of human or animal origin, such as caprine monocytes [69] and murine macrophages [70]. Also, Halvorsen and colleagues demonstrated that EPA increased adhesion of bacteria to human monocytes, indicating a positive effect on phagocytosis [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, the present study is the first to address the effects of ω3 FAs on microglial phagocytosis of A␤ 42 and on their M1/M2 phenotype. Several studies have shown stimulatory effects of ω3 FAs on other types of phagocytic cells of human or animal origin, such as caprine monocytes [69] and murine macrophages [70]. Also, Halvorsen and colleagues demonstrated that EPA increased adhesion of bacteria to human monocytes, indicating a positive effect on phagocytosis [71].…”
Section: Discussionmentioning
confidence: 99%
“…Infected macrophages were then lysed with ddH 2 O containing 0.5% Triton X-100 (ref. 53). The cell lysates were then serially diluted, and 100 ml of each dilution was plated on triplicate LB agar plates and incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…an increase in membrane unsaturated fatty acid content is correlated with an increase in phagocytosis rate (Fig. 2) (Adolph et al, 2012a;Calder et al, 1990;Davidson et al, 1998;Fuhrmann et al, 2007;Lecchi et al, 2011;Schroit and Gallily, 1979;Zheng et al, 1999). Available in vivo-data are less clear.…”
Section: Modulation Of Phagocytosis By Fatty Acidsmentioning
confidence: 90%
“…Fatty acids have been found to influence every type of immune cell in a variety of ways (Calder, 2008), regard to macrophage function the fatty acids are reported to modulate all of the known defense mechanisms of these cells including phagocytosis, respiratory burst, cytokine production and antigen presentation (Adolph et al, 2012a(Adolph et al, , 2012bSchoeniger et al, 2011). So far, tremendous effort has been put into enlightening the different effects of individual fatty acids and several fatty acid families as well as into elucidating the underlying mechanisms of action.…”
Section: Fatty Acids and The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation